The 2024 Reclaim the Night Movement Following the Kolkata Rape and Murder Case: A Framing Theory Analysis - Muhammad Erza Aimar Rizky; Timothy Sandro Yusuf; Josepha Caroline Sekarningrum Rijadi; Muhammad Dafa Ramadhan; Ghazy Abiyyu Dary Adhipramana (Universitas Pelita Harapan, 2025)
The “Reclaim the Night” (RTN) movement in India, galvanized by the 2024 Kolkata rape and murder case, exemplifies the dynamic interaction between grassroots activism and collective action framing in addressing systemic gender-based violence. This study investigates the dynamics of the collective action framing process within the 2024